2019
DOI: 10.1002/jsfa.9536
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the binding interaction of Maillard reaction by‐product 5‐hydroxymethyl‐2‐furaldehyde with calf thymus DNA

Abstract: BACKGROUND 5‐Hydroxymethyl‐2‐furaldehyde (5‐HMF), a by‐product of the Maillard reaction, usually present in fried and baked food, may cause potential harm to the human body. Here, the interaction between 5‐HMF and calf thymus DNA (ctDNA) under physiological buffer (pH 7.4) was studied using multi‐spectroscopic methods combined with multivariate curve resolution–alternating least squares (MCR‐ALS) chemometrics and molecular simulation techniques. RESULTS The concentration profiles and pure spectra of the three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 55 publications
(94 reference statements)
1
4
0
Order By: Relevance
“…As seen from Figure 4 , the conformations with the highest number of binding times (45 times, −4.44 kcal mol −1 ) were obtained for final binding analysis ( Figure 4A ). It can be found that the lowest binding energy predicted by molecular simulation (−4.44 kcal mol −1 = −18.57 kJ mol −1 ) is slightly higher than that measured by thermodynamic experiments (−27.35 kJ mol −1 ), which may be due to the lack of desolvation energy in the vacuum environment of docking operation, similar results have been found in previous studies (Zhou et al, 2019 ). As seen from Figure 4B , NAA is bound with ctDNA in the groove region which is rich in G–C bases.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…As seen from Figure 4 , the conformations with the highest number of binding times (45 times, −4.44 kcal mol −1 ) were obtained for final binding analysis ( Figure 4A ). It can be found that the lowest binding energy predicted by molecular simulation (−4.44 kcal mol −1 = −18.57 kJ mol −1 ) is slightly higher than that measured by thermodynamic experiments (−27.35 kJ mol −1 ), which may be due to the lack of desolvation energy in the vacuum environment of docking operation, similar results have been found in previous studies (Zhou et al, 2019 ). As seen from Figure 4B , NAA is bound with ctDNA in the groove region which is rich in G–C bases.…”
Section: Resultssupporting
confidence: 86%
“…The preparation method of ctDNA (Sigma Chemical Reagent Co., Ltd., USA) reserve solution is as follows: dissolve the appropriate amount of ctDNA in 0.1 mol L −1 NaCl solution and shake it gently until it dissolves. Then determine the ratio of ultraviolet absorbance of ctDNA reserve solution at 260 and 280 nm to 1.91 ( A 260 / A 280 = 1.91>1.8), indicating that the purity of ctDNA concentrate meets the requirements (Zhou et al, 2019 ). Finally, the absorbance value of ctDNA solution at 260 nm was determined, and the concentration in the reserve solution was calculated to be 3.22 × 10 −3 mol L −1 by using molar absorbance coefficient ε 260 = 6,600 L mol −1 cm −1 .…”
Section: Methodsmentioning
confidence: 99%
“…It is generally believed that HMF is formed by the thermal decomposition of carbohydrates. Recent studies have shown that the Maillard reaction is an important way for the production of HMF in food 34‐36 . Thus, a reduced level of HMF in food products could reduce the health risks to the consumer 37 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that the Maillard reaction is an important way for the production of HMF in food. [34][35][36] Thus, a reduced level of HMF in food products could reduce the health risks to the consumer. 37 From Table 2, it is seen that the HMF content in dried jujubes varied with the variation of pretreatment.…”
Section: Effective Moisture Diffusivitymentioning
confidence: 99%
“…The initial snapshot of the MD process is shown in Figure 8A. Root mean square deviation (RMSD) is an important indicator to calculate the deviation of Cα backbone atoms from the overlap of the instantaneous structures (Brogi et al, 2020;Wang et al, 2015a;Zhou et al, 2018). A smaller deviation represents a higher spatial equivalent of the compared structures.…”
Section: Results Of MD Simulationmentioning
confidence: 99%